Perceptions of Students in Public Speaking Activities at The Salman Assalam Islamic Boarding School in Cirebon - Awang Setiya Permana; Sri Wulandari; Welly Wihayati (Greenation International Journal of Law and Social Sciences, 2026)
Public speaking is one of the most essential communication skills in both social and religious life (Lucas, 2019). Within the context of the boarding school environment, this skill functions not only as a means of conveying ideas, but also as a medium for developing self-confidence, leadership, and the ability to communicate Islamic values effectively (Harvy Ghaufar & Foreza, 2020; Muttaqin et al., 2025). In practice, not all students share the same perceptions of public speaking activities, since perception is influenced by cognitive, emotional, and social factors (OpenStax, 2020; Röhner & Schütz, 2023). This study aims to examine the implementation of public speaking activities at Salman Assalam Islamic boarding school Cirebon, to identify the obstacles encountered during their implementation, and to analyze students’ perceptions of these activities as part of the process of developing communication skills in the boarding school educational setting. This research employs a descriptive qualitative approach (Creswell, 2014), as its primary objective is to gain an in-depth understanding of students’ perceptions of public speaking activities at Salman Assalam Islamic boarding school Cirebon. The research data were collected through in-depth interviews and direct observation of students involved in public speaking activities. Data analysis was conducted through three main stages: data reduction, data display, and conclusion drawing and verification (Miles & Huberman, 1994). Overall, the findings indicate that public speaking activities at Salman Assalam Islamic boarding school Cirebon serve not only as training for speaking in public, but also as a platform for shaping students’ communicative character through the sensory, cognitive, emotional, and social experiences they undergo (OpenStax, 2020). These four dimensions of perception are interconnected and form a comprehensive understanding of how students evaluate, experience, and respond to the process of communication learning in the boarding school. The success of public speaking activities is strongly influenced by the support of instructors, a conducive learning environment, and students’ reflective experiences at each stage of implementation (Aziz et al., 2020; Röhner & Schütz, 2023). In general, public speaking activities play a significant role in fostering self-confidence, communication skills, and students’ character in accordance with the educational values upheld by Salman Assalam Islamic Boarding School Cirebon.